UMPSA celebrates students’ excellence in 2024 Mercu Sanjung Awards Night - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 16 April 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to reinforce its commitment to producing holistic and competitive students as 28 recipients were honoured at the 2024 Mercu Sanjung Awards Night (MARS) held at the UMPSA Gambang Campus Sports Complex Hall.